2020
DOI: 10.3390/su12197872
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Sustainability Assessment into Decoupling Analysis: A Focus on the Yangtze River Delta Urban Agglomerations

Abstract: Rapid urbanization has led to a growing number of environmental challenges in large parts of China, where the Yangtze River Delta (YRD) urban agglomerations serve as a typical example. To evaluate the relationship between environmental sustainability gaps and urbanization in 26 cities of the YRD, this study revisited the environmental sustainability assessment (ESA) by combining the metrics of environmental footprints and planetary boundaries at the city level, and then integrated the footprint-boundary ESA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…(2016) was not a simple adoption of the mainstream methods but instead proposed a useful quantification approach that was more appropriate than mainstream methods for their specific study area and research purpose. We also found that studies performed at smaller scales could reveal the changes in the water PB and state as well as the water‐use sustainability over time (Dong et al., 2021; Y. J. Huang et al., 2020; Yang & Cheng, 2021); these factors are relatively difficult to assess at larger scales.…”
Section: Resultsmentioning
confidence: 83%
“…(2016) was not a simple adoption of the mainstream methods but instead proposed a useful quantification approach that was more appropriate than mainstream methods for their specific study area and research purpose. We also found that studies performed at smaller scales could reveal the changes in the water PB and state as well as the water‐use sustainability over time (Dong et al., 2021; Y. J. Huang et al., 2020; Yang & Cheng, 2021); these factors are relatively difficult to assess at larger scales.…”
Section: Resultsmentioning
confidence: 83%
“…With the acceleration of urbanization, urban agglomeration has gradually become an important development model, and more and more scholars have studied the sustainable development of a certain region or urban agglomeration (Tan et al, 202;Zinatizadeh et al, 2017), mainly focusing on China's Yangtze River Delta urban agglomeration (Huang et al, 2020), Beijing-Tianjin-Hebei urban agglomeration (Chen et al, 2019), Chengdu-Chongqing urban agglomeration (Cheng et al, 2020), the Yangtze River urban agglomeration (Gu et al, 2015;Luo et al, 2021), etc. In addition, in recent years, research on the sustainable development of foreign urban agglomerations has gradually emerged (Butsch et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is now a modest growth industry in downscaled PBs, DPBs [71][72][73], which have been proposed as ways of distributing responsibility for the planet down to regional and local levels where citizens might more readily become engaged: "Think globally, act locally." As with sustainability indicators, a literature assessing DPBs is emerging [64,74].…”
Section: Management Of Extraordinary Risksmentioning
confidence: 99%